Seasonality of the mass concentration and chemical composition of aerosols around an urbanized basin in East Asia. Issue 3 (11th February 2017) - Chou, C. C.‐K.; Hsu, W.‐C.; Chang, S.‐Y.; Chen, W.‐N.; Chen, M.‐J.; Huang, W.‐R.; Huang, S.‐H.; Tsai, C.‐Y.; Chang, S.‐C.; Lee, C.‐T.; Liu, S.‐C.
Abstract: This study investigated seasonal variations in the mass concentration and chemical composition of ambient aerosols observed at three stations (coastal, mountainous, and downtown sites) in northern Taiwan from March 2009 to February 2012. The results show that the major aerosol components include ammonium, sulfate, nitrate, sea salt, dust, organic carbon, and elemental carbon, whereas the mass fraction of each species depends on the sampling location and season. A significant correlation ( r  = 0.7–0.8) was observed in aerosol concentrations measured at the respective stations, indicating that aerosol concentrations were dominated by regional‐scale factors. Ammonium, sulfate, and nitrate consistently reached respective peak values in the spring in conjunction with dust particle levels. This shows that the transport of dust and particulate air pollutants from the Asian continent has affected the atmospheric environment in this area. Distinct seasonality was observed for sea salt and secondary organic carbon (SOC): sea salt levels peaked in the autumn, whereas SOC levels peaked in the summer, implying that their sources were regulated by independent seasonal factors. Correlation between sea salt concentration and surface wind speed was derived from coastal measurements and showed a high value for the wind speed sensitivity parameter of around 0.37 for our location. In addition, it was revealed that the SOC concentration in aerosols was positively correlated with oxidant photolysis index (O x  × UVB), suggesting that the SOC seasonality was dominated by hydroxyl radical production. Key Points: Inorganic particulate pollutants and dust consistently peaked in the spring due to Asian outflow effects Ambient concentrations of sea salt particles were exponentially correlated with surface wind speeds The production of secondary organic aerosols was dominated by the photolysis of total oxidants